Psychiatrist and Psychologist Experiences with Telehealth and Remote Collaborative Care in Primary Care: A Qualitative Study. Issue 4 (6th October 2020) - Howland, Molly; Tennant, McKenna; Bowen, Deborah J.; Bauer, Amy M.; Fortney, John C.; Pyne, Jeffrey M.; Shore, Jay; Cerimele, Joseph M.
Abstract: Purpose: Availability of mental health services is limited in the rural United States. Two promising models to reach patients with limited access to care are telehealth referral and collaborative care. The objective of this study was to assess telepsychiatrist‐ and telepsychologist‐level facilitators and barriers to satisfaction with and implementation of these 2 telehealth models in rural settings. Methods: Focus groups were held in 2019 using a semistructured interview guide. Participants were off‐site telepsychiatrists (N = 10) and telepsychologists (N = 4) for primary care clinics across 3 states (Washington, Michigan, and Arkansas) involved in a recent pragmatic comparative effectiveness trial. Qualitative analysis occurred inductively by 2 independent coders. Findings: Participants were satisfied with the models partly owing to good patient rapport and expanding access to care. Teamwork was highlighted as a facilitator in collaborative care and was often related to work with care managers. However, participants described communication with primary care providers as a challenge, especially in the telehealth referral arm. Barriers centered on variability of logistical processes (eg, symptom monitoring, scheduling, electronic medical record processes, and credentialing) among sites. Staff turnover, variable clinic investment, and inadequacy of training were possible explanations for these barriers. Conclusions: Participants described high motivation to provide team‐based, remote care for patients, though they experienced operational challenges. Centralized credentialing, scheduling, and record keeping are possible solutions. These findings are important because consulting psychiatrists and psychologists may play a leadership role in the dissemination of these models.